А legal adjusting of providing of the rights for children-invalids in Ukraine - Bodnarchuk, Ihor; Udych, Anton (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The article is devoted to the legal regulation of the rights of children with disabilities in Ukraine. The article considers the international legal status of the child and the status of a disabled person. The characteristic features on which a person with disabilities can be considered invalid is considered. Given the fact that disability has several criteria – social, medical and legal, in the article special attention is paid to the legal, which is based on the constitutional equality of rights and the inadmissibility of discrimination on the basis of disability. The article substantiates that the introduction of an inclusive form of education in educational institutions should ensure the full realization of the rights of children with disabilities to receive education